OPTIMIZATION OF COMMERCIAL GRADE NaHCO3 (MITHA SODA) CONCENTRATION FOR SPIRULINA FUSIFORMIS CULTIVATION - ANURADHA SHARMA, (The Bioscan, 2012)
As a food supplement Spirulina is gaining more and more attention. Its growing demand has led to its large scale cultivation, which had been a very costly affair and low cost nutrient are mandatory to minimize its economy. The present experiment was conducted to find out the optimum concentration of commercial grade NaHCO3 i.e. mitha soda in CFTRI (I) medium for supporting the highest yield of Spirulina fusiformis. Algal samples with 4.5 g/L -10g/L concentration of mitha soda in CFTRI (I) medium were prepared and algal growth was recorded in terms of optical density upto the 25th day. Present experiment revealed that 6g/L concentration of mitha soda successfully proved to be better for the growth of Spirulina fusiformis. From the economy point of view, cost input for 6g/L mitha soda was 5 times cheaper than the analytical grade NaHCO3.